(untitled) (Research, Society and Development, 2025)
The recognition of rare genetic diseases has become a growing concern on the global stage, affecting around 8% of the world’s population and 13 million people in Brazil. Among the approximately 6 to 8 thousand rare diseases, 95% do not have specific treatment. Mosaic trisomy 17 is one such rare condition, with only 28 cases detected by amniocentesis. Its clinical presentation is highly variable, and diagnosis is made by prenatal and postnatal karyotyping. Most cases do not present with anomalies, and many are attributed to placental mosaicism. Trisomy 17 is difficult to diagnose and often overlooked. The objective of the present study was to carry out an exploratory descriptive study, based on a narrative bibliographic review, to characterize chromosome mosaic trisomy 17, using scientific articles published between 2000 and 2020. Data were collected in databases such as PubMed, SciELO and Periódicos CAPES. The study detailed signs and symptoms associated with the condition, identifying anomalies in the bones, face, heart and other organs, with diagnoses using amniocentesis, skin fibroblasts and fetal ultrasound. The study concludes that rare genetic diseases, such as trisomy 17, are still little addressed in Public Health, although they represent an important public health problem. The need for greater dissemination and understanding of these conditions is highlighted, aiming to improve awareness and early diagnosis.